Colonising myths-Maori realities: He rukuruku whakaaro - Mikaere, Ani (Huia Publishers, 2011)

Making our place: exploring land-use tensions in Aotearoa New Zealand - Ruru, Jacinta; Abbott, Mick; Stephenson, Janet (Otago University Press, 2011)
Keywords: colonisation; economic aspects; environment; land tenure; land use; social aspects; treaty negotiations

Always Speaking: The Treaty of Waitangi and Public Policy - Tawhai, Veronica; Gray-Sharp, Katarina (Huia Publishers, 2011)
This is a collection of papers that examine the current place of the Treaty of Waitangi in core public policy areas. The authors analyse the tensions and dynamics in the relationship between Maori and the Crown in their areas of expertise, detail the key challenges being faced, and provide insights on how these can be overcome. The policy areas covered in the collection span the environment, Maori and social development, health, broadcasting, the Maori language, prison and the courts, local government, research, science and technology, culture and heritage, foreign affairs, women's issues, labour, youth, education, economics, housing and the electoral system.
Keywords: civil Rights

Indigenous Peoples and Demography: The Complex Relation between Identity and Statistics - Chapter 2 Building ethnic boundaries in New Zealand; representations of Maori identity in the census - Kukutai, Tahu (Berghahn Books, 2011)
When researchers want to study indigenous populations they are dependent upon the highly variable way in which states or territories enumerate, categorise and differentiate indigenous people. In this volume, anthropologists, historians, demographers and sociologists have come together for the first time to examine the historical and contemporary construct of indigenous people in a number of fascinating geographical contexts around the world, including Canada, the United States, Colombia, Russia, Scandinavia, the Balkans and Australia. Using historical and demographical evidence, the contributors explore the creation and validity of categories for enumerating indigenous populations, the use and misuse of ethnic markers, micro-demographic investigations, and demographic databases, and thereby show how the situation varies substantially between countries.
Keywords: anthropology; census; crown policy; ethnic identity